NILAI KESANTUNAN DALAM MANTRA MEOLI - Heksa Biopsi Puji Hastuti (SUAR BETANG, 2017)
Meoli spell present as one performance package within custom ritual called meoli ritual. Meoli ritual is a politeness expression of the perpetrators in expressing the purpose of request permission or apology to the sangia as the ruler of nature when opening the land to grow crops. This study examines the value of politeness in the meoli spell with the ethnopoetic approach. The issues raised are how has the politeness value existed in the meoli spell. By applying qualitative research method, data collection is done by observation, interview, and literature study. From the analysis, it is known that the value of politeness in the meoli mantra embodies the priority scale in which the preferred is the custom observer, followed by an apology by mentioning the whole of the target, newly expressed by the expression of intent and hope as the core message of the meoli spell. The beautiful way of disclosure also supports the value of politeness in the meoli spell